Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 201966 by mnjuly1970 last updated on 17/Dec/23

         solve           ((x^2 +3x+2))^(1/3)  (((x+1))^(1/3)  −((x+2))^(1/3)  )= 1

$$ \\ $$$$\:\:\:\:\:\:\:{solve}\: \\ $$$$\:\: \\ $$$$\:\:\:\:\sqrt[{\mathrm{3}}]{{x}^{\mathrm{2}} +\mathrm{3}{x}+\mathrm{2}}\:\left(\sqrt[{\mathrm{3}}]{{x}+\mathrm{1}}\:−\sqrt[{\mathrm{3}}]{{x}+\mathrm{2}}\:\right)=\:\mathrm{1} \\ $$$$ \\ $$

Answered by ajfour last updated on 17/Dec/23

let  x+(3/2)=t  ⇒  p=x+1=t−(1/2)  q=x+2=t+(1/2)  ⇒ −R= x^2 +3x+2=t^2 −(1/4)  pq=−R  (t^2 −(1/4))[−1−((3(pq)^(1/3) )/((t^2 −(1/4))^(1/3) ))]=1  −1−((3(pq)^(1/3) )/((t^2 −(1/4))^(1/3) ))=  −(1/R)  ((1/R)−1)^3 =((27(−R))/(−R))  ⇒  (1/R)−1=3  ⇒  R=(1/4)       x^2 +3x+2=−(1/4)  x^2 +3x+(9/4)=0  (x+(3/2))^2 =0  x= −(3/2)

$${let}\:\:{x}+\frac{\mathrm{3}}{\mathrm{2}}={t}\:\:\Rightarrow\:\:{p}={x}+\mathrm{1}={t}−\frac{\mathrm{1}}{\mathrm{2}} \\ $$$${q}={x}+\mathrm{2}={t}+\frac{\mathrm{1}}{\mathrm{2}} \\ $$$$\Rightarrow\:−{R}=\:{x}^{\mathrm{2}} +\mathrm{3}{x}+\mathrm{2}={t}^{\mathrm{2}} −\frac{\mathrm{1}}{\mathrm{4}} \\ $$$${pq}=−{R} \\ $$$$\left({t}^{\mathrm{2}} −\frac{\mathrm{1}}{\mathrm{4}}\right)\left[−\mathrm{1}−\frac{\mathrm{3}\left({pq}\right)^{\mathrm{1}/\mathrm{3}} }{\left({t}^{\mathrm{2}} −\frac{\mathrm{1}}{\mathrm{4}}\right)^{\mathrm{1}/\mathrm{3}} }\right]=\mathrm{1} \\ $$$$−\mathrm{1}−\frac{\mathrm{3}\left({pq}\right)^{\mathrm{1}/\mathrm{3}} }{\left({t}^{\mathrm{2}} −\frac{\mathrm{1}}{\mathrm{4}}\right)^{\mathrm{1}/\mathrm{3}} }=\:\:−\frac{\mathrm{1}}{{R}} \\ $$$$\left(\frac{\mathrm{1}}{{R}}−\mathrm{1}\right)^{\mathrm{3}} =\frac{\mathrm{27}\left(−{R}\right)}{−{R}} \\ $$$$\Rightarrow\:\:\frac{\mathrm{1}}{{R}}−\mathrm{1}=\mathrm{3}\:\:\Rightarrow\:\:{R}=\frac{\mathrm{1}}{\mathrm{4}} \\ $$$$\:\:\:\:\:{x}^{\mathrm{2}} +\mathrm{3}{x}+\mathrm{2}=−\frac{\mathrm{1}}{\mathrm{4}} \\ $$$${x}^{\mathrm{2}} +\mathrm{3}{x}+\frac{\mathrm{9}}{\mathrm{4}}=\mathrm{0} \\ $$$$\left({x}+\frac{\mathrm{3}}{\mathrm{2}}\right)^{\mathrm{2}} =\mathrm{0} \\ $$$${x}=\:−\frac{\mathrm{3}}{\mathrm{2}} \\ $$

Commented by mnjuly1970 last updated on 17/Dec/23

  thanks alot sir ajfor

$$\:\:{thanks}\:{alot}\:{sir}\:{ajfor} \\ $$$$\:\: \\ $$

Answered by Frix last updated on 17/Dec/23

(ab)^(1/3) (a^(1/3) −b^(1/3) )=1  a^(1/3) −b^(1/3) _(★) =(ab)^(−(1/3))   a−3(ab)^(1/3) (a^(1/3) −b^(1/3) _(★) )−b=(ab)^(−1)   a−b−3=(1/(ab))  a=x+1∧b=x+2  x^2 +3x+(9/4)=0  x=−(3/2)  [Only true if we stay ∈R ⇒ ((−r))^(1/3) =−(r)^(1/3) ]

$$\left({ab}\right)^{\frac{\mathrm{1}}{\mathrm{3}}} \left({a}^{\frac{\mathrm{1}}{\mathrm{3}}} −{b}^{\frac{\mathrm{1}}{\mathrm{3}}} \right)=\mathrm{1} \\ $$$$\underset{\bigstar} {\underbrace{{a}^{\frac{\mathrm{1}}{\mathrm{3}}} −{b}^{\frac{\mathrm{1}}{\mathrm{3}}} }}=\left({ab}\right)^{−\frac{\mathrm{1}}{\mathrm{3}}} \\ $$$${a}−\mathrm{3}\left({ab}\right)^{\frac{\mathrm{1}}{\mathrm{3}}} \left(\underset{\bigstar} {\underbrace{{a}^{\frac{\mathrm{1}}{\mathrm{3}}} −{b}^{\frac{\mathrm{1}}{\mathrm{3}}} }}\right)−{b}=\left({ab}\right)^{−\mathrm{1}} \\ $$$${a}−{b}−\mathrm{3}=\frac{\mathrm{1}}{{ab}} \\ $$$${a}={x}+\mathrm{1}\wedge{b}={x}+\mathrm{2} \\ $$$${x}^{\mathrm{2}} +\mathrm{3}{x}+\frac{\mathrm{9}}{\mathrm{4}}=\mathrm{0} \\ $$$${x}=−\frac{\mathrm{3}}{\mathrm{2}} \\ $$$$\left[\mathrm{Only}\:\mathrm{true}\:\mathrm{if}\:\mathrm{we}\:\mathrm{stay}\:\in\mathbb{R}\:\Rightarrow\:\sqrt[{\mathrm{3}}]{−{r}}=−\sqrt[{\mathrm{3}}]{{r}}\right] \\ $$

Commented by Frix last updated on 17/Dec/23

...and no complex solutions.

$$...\mathrm{and}\:\mathrm{no}\:\mathrm{complex}\:\mathrm{solutions}. \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com